2020
DOI: 10.1186/s12987-020-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 and the Na+/K+/2Cl− cotransporter 1 are present in the leptomeningeal vasculature of the adult rodent central nervous system

Abstract: Background: The classical view of cerebrospinal fluid (CSF) production posits the choroid plexus as its major source. Although previous studies indicate that part of CSF production occurs in the subarachnoid space (SAS), the mechanisms underlying extra-choroidal CSF production remain elusive. We here investigated the distributions of aquaporin 1 (AQP1) and Na + /K + /2Cl − cotransporter 1 (NKCC1), key proteins for choroidal CSF production, in the adult rodent brain and spinal cord. Methods: We have accessed AQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…We adapted our tool from clinical practice to provide a range of options for measuring global cerebral fluid states that reflect the interaction between CSF and cranial tissues. In later life, CSF homeostasis is maintained by collaborative efforts from multiple putative players in the brain, including the ChP, the dural lymphatics 14 , leptomeningeal vasculature 77 , and the ependyma 78 . While this approach measures overall cranial fluid dynamics as one single unit, future applications could apply mathematical models that have been proposed to isolate the contribution of distinct CSF outflow routes using data acquired from patients 79 .…”
Section: Discussionmentioning
confidence: 99%
“…We adapted our tool from clinical practice to provide a range of options for measuring global cerebral fluid states that reflect the interaction between CSF and cranial tissues. In later life, CSF homeostasis is maintained by collaborative efforts from multiple putative players in the brain, including the ChP, the dural lymphatics 14 , leptomeningeal vasculature 77 , and the ependyma 78 . While this approach measures overall cranial fluid dynamics as one single unit, future applications could apply mathematical models that have been proposed to isolate the contribution of distinct CSF outflow routes using data acquired from patients 79 .…”
Section: Discussionmentioning
confidence: 99%
“…AQP1 is mainly expressed on the apical and basolateral surfaces of the choroid plexuses and plays a role in CSF production 100 . Acetazolamide may reduce CSF production by inhibiting AQP1 and thus slow the development of hydrocephalus.…”
Section: Aquaporin Regulation Treatment For Hydrocephalusmentioning
confidence: 99%
“…AQP1 is mainly expressed on the apical and basolateral surfaces of the choroid plexuses and plays a role in CSF production. 100 Acetazolamide may reduce CSF production by inhibiting AQP1 and thus slow the development of hydrocephalus. However, a study in six dogs with internal hydrocephalus showed that acetazolamide treatment was not effective in inhibiting ventricular dilation.…”
Section: Aquaporin Regulation Treatment For Hydrocephalusmentioning
confidence: 99%
“…They found that AQP1 is expressed in the vasculature of the adult rodent brain. The results shed new light on extrachoroidal cerebrospinal fluid production [62].…”
Section: Techniquesmentioning
confidence: 99%